Weight loss promoted by the Intra-oral Alimentary Satiety Device in a morbidly obese patient - HALMENSCHLAGER,Mariane (2015)
OBJECTIVE: To evaluate the weight loss fostered by the Intra-oral Alimentary Satiety Device in a patient diagnosed as morbidly obese. METHODS: A female patient diagnosed as morbidly obese who was seeing a nutritionist was examined. Based on her medical history and anthropometric assessment, a hypocaloric diet was prescribed. The nutritional state was assessed by the Body Mass Index (BMI). The patient was advised to wear the Intra-oral Alimentary Satiety Device, and an assessment by a dentist was suggested to discard contraindications. The appliance was then manufactured with dental molding material, orthodontic stainless steel wire, and heat-cured dental acrylic resin. The patient wore the device at every meal, putting it on 5 minutes in advance. For the data analysis the SPSS Statistics 17.0 software was used. RESULTS: In her first consultation, the patient weighed 115 kg and was 1.62 m tall, with BMI = 43.82 Kg/m. Weight loss was 13.3 kg, representing 11.57% of the initial weight. In relation to the BMI, the total loss was 5.06 Kg/m, representing 11.55%. CONCLUSION: The Intra-oral Alimentary Satiety Device can be considered a safe and effective method which, together with a hypocaloric diet, shows satisfactory results, thus proving to be an important auxiliary option in the treatment of obesity.